Preparation and Study of Undoped and Al-Doped on The Structure and the Optical Properties of In₂S₃ Thin Film - Mohammed Abdullah, Dhuha; Hussein, Bushra H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Undoped and aluminum-doped In2S3 chalcopyrite semiconductor thin films are deposited on glass substrates using the thermal evaporation process under a vacuum of 1.6×10^-5 mbar, achieving a thickness of 500 nm. This study examines the impact of varying Al ratios of 0.0, 0.02 and 0.04 on properties of Al-doped In2S3 thin film. The structural characteristics of In2S3 thin films were studied by X-ray diffraction (XRD) and atomic force microscopy (AFM), revealing that the In2S3 film exhibits a polycrystalline structure and stable tetragonal β-In2S3, with a preferred orientation of (109) at 2θ = 27.3. Furthermore, AFM is examining the exterior morphology of the film, revealing that both surface roughness and average diameter escalate with higher Al ratios, hence augmenting the crystallite size of the thin films. The UV/Vis spectrophotometer analyzed the optical properties of In2S3 films, revealing a maximum absorbance of 90% in the visible spectrum and a minimum transmittance. The films exhibited a bandgap that decreased by 0.04 for each ratio of Al, ultimately reaching a minimum value of Semiconductors In2S3 possess straight band gaps of 2.05, 1.98, and 1.95 eV, respectively. The computed optical constant encompasses the refractive index and the extinction coefficient. Real and imaginary components of the dielectric constant.